Library archetypes: design of a multimedia didactic proposal that contributes to the improvement of the image of librarianship in Costa Rican society - Oviedo González, Freddy Alonso (2012)
This document describes each one of the steps of the investigation carried out to know the factors that could be influencing the low enrollment of first-time students that the School of Librarianship, Documentation and Information of the National University has experienced in the last few years. In response to the needs detected, a multimedia-didactic proposal is proposed, which contributes to improving the problems encountered, making use of technological tools with a pedagogical basis that encourages reflection of the population to whom the product is directed. Finally, the conclusions and recommendations obtained in the study are presented.